Against Bullying through Cultural Awareness: Establishing a School Environment that Promotes Respect and Inclusivity - Rismayani, Rismayani (EDUPEDIA Publisher, 2024)
Multifaceted forms of bullying, including physical, verbal, social, and cyber, significantly affect the general well-being and academic performance of student communities. In many educational institutions worldwide, persistent bullying remains a significant barrier, impacting the psychological, emotional, and physical well-being of students (Debarbieux, 2001; Guerra C. et al., 2011). Intentional injury is the willful or failure to act those harms individuals connected with the educational community, teaching staff, student body, and other staff members (Serrano & Iborra, 2005). The existence of bullying in educational institutions has multiple detrimental effects on the students who are subjected to it, therefore increasing the probability of students becoming disengaged from the learning process systematically. Failing to confront bullying appropriately may lead to its consequences impacting multiple facets. Incidents of bullying at educational institutions can lead to reduced academic achievement, increased levels of stress, and social or physical seclusion, finally resulting in suicide and death. Cultural awareness encompasses recognizing, demonstrating respect for, and valuing everyone’s diverse cultural, ethnic, and socioeconomic backgrounds. Implementing cultural knowledge in educational environments is a crucial strategy to address and prevent bullying. Given the increasing variety within our educational institutions, fostering an environment that emphasizes respect and inclusivity is crucial.